Measurement by the physical educator why and how - Miller, David K. (David Keith) (McGraw-Hill Education, 2020)
Students in measurement and evaluation classes often are bombarded with an abundance of information. Regrettably, some students complete the class with a little knowledge in many areas but no confidence or skills to perform the procedures and techniques presented in the class. As professionals in school or nonschool settings, these same students often do not measure and assess knowledge, and physical performance, in the proper way